Experimental Study on Mechanical Deformation and Energy Evolution of Deep Coal Under Complex Stress Paths - Yue Jiang; Xingfeng Mao; Dongming Zhang; Xiang Yang (Applied Sciences, 2025)
This study proposes a novel cyclic stress path with simultaneous axial and confining stress and conducts triaxial testing on raw coal over various cycle periods. The analysis of bias stress–strain curves, deformation parameters, and energy indexes elucidated the mechanical and energy evolution patterns of coals under novel stress routes. The three deformation parameters can well reflect the deformation characteristics of the specimens. The last few cycles saw an increase in Poisson’s ratio and irreversible deformation, indicating that the coal samples were likely to crack. Specimens are more prone to instability and destruction due to increased expansion under high frequency loading. To explore the energy evolution, the energy percentage and damping ratio are added to the previously mentioned basic energy indexes. Faster cyclic period reduces specimen microstructure stability, increases mineral particle misalignment friction, and raises dissipated energy percentage and damping ratio. <semantics>DS</semantics> and <semantics>Dd</semantics> based on deformation parameters and cumulative dissipated energy, respectively, can characterize the coal’s three damage stages of “deceleration–stabilization–acceleration”. Both damage variables accumulate faster in the acceleration damage stage due to cyclic period acceleration.